Surrogate motherhood: Proposed legislation eagerly awaited - H. Oosthuizen; T. Verschoor (South African Family Practice)
The inabitity to bear a child by natural meansis a common phenomenon in modern times. Surogacy has become an acceptable option for many. The surogate mother can be the recipient of a fertilised embryo, or she can be impregnated by the sperm of the childless couple's male partner. A surrogacy agreement can pose many ethical ancl legal questions, making clear guidelines essential. The proposed Act on Surrogate Motherhood of 1994 contains these guidelines within which sunogace agreements can function, but has yet to materialise.